The Effect of Information Asymmetry towards Conditional and Unconditional Conservatism (A study on Trade, Services, and Investment Sector from IDX Listed Companies in 2018-2020) - Catra Lestari Rachmawati; Fuad Fuad (Diponegoro Journal of Accounting, 2022)
The purpose of this study is to examine if the information asymmetry affects conditional and unconditional conservatism he data used in this study uses secondary data taken from the company's annual reports that is provided in Indonesian Stock Exchange website and Indonesian Stock Exchange statistics data from 2018 to 2020. Multiple linear regression was used as the analytical method. The results of the analysis show that one hypothesis is the information asymmetry and control variables that are dimensioned by total assets affect the conditional conservatism. While the results of the second hypothesis show that the information asymmetry and control variables that are dimensioned by total assets, do not affect unconditional conservatism.